COVID-19: EFEK PADA SAHAM YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX (JII) - Vivi Indah Bintari; Deasy Lestary Kusnandar (Procuratio : Jurnal Ilmiah Manajemen, 2022)
COVID-19 has affected communities, businesses and organizations globally, automatically affecting financial markets and economies. This led to a significant decline in capital market conditions in Indonesia. Therefore, the Indonesia Stock Exchange issued an announcement on the decision letter of the board of directors of the Indonesia Stock Exchange regarding changes in trading times regarding exchange transactions, regarding the development of global capital market conditions and the Indonesian capital market which are under pressure, among others, influenced by the determination of the corona virus (COVID-19) as global pandemic by WHO. With a country where the majority of the people are Muslim, the indicators or instruments of sharia shares on the IDX are interesting things to study carefully. This study aims to examine how the COVID-19 outbreak has affected companies listed on the Jakarta Islamic Index (JII). The study period was classified into the period before and after the announcement. The data consists of 30 daily price observations from 30 selected companies. The research period ranges from March 4, 2020 to April 17, 2020. The test was carried out using a different paired sample t-test with SPSS 26 software. The results of the study indicate that there is a significant difference in returns between before and after the announcement of the decision letter of the board of directors of the Indonesia Stock Exchange. regarding changes in trading times regarding exchange transactions, regarding developments in global capital market conditions and the Indonesian capital market which is under pressure, among others influenced by the determination of the corona virus (COVID-19) as a global pandemic by WHO in the Jakarta Islamic Index (JII). COVID-19 telah memengaruhi komunitas, Bisnis, dan organisasi secara global, yang secara otomatis mempengaruhi pasar keuangan dan ekonomi. Hal tersebut menyebabkan terjadinya penurunan yang signifikan pada kondisi pasar modal di Indonesia. Sehingga Bursa Efek Indonesia mengeluarkan pengumuman surat keputusan dewan direksi Bursa Efek Indonesia mengenai perubahan waktu perdagangan tentang transaksi pertukaran, mengenai perkembangan kondisi pasar modal global dan pasar modal Indonesia yang berada di bawah tekanan, antara lain dipengaruhi oleh penentuan virus korona (COVID-19) sebagai pandemi global oleh WHO. Dengan negara yang mayoritas masyarakatnya beragama Islam menjadikan indikator atau instrumen saham syariah di BEI menjadi hal yang menarik untuk dikaji dengan teliti. Penelitian ini bertujuan untuk menguji bagaimana wabah COVID-19 telah mempengaruhi perusahaan yang terdaftar di Jakarta Islamic Index (JII). Periode studi diklasifikasikan ke dalam periode sebelum dan setelah pengumuman. Data terdiri dari 30 observasi harga harian dari 30 perusahaan terpilih. Periode penelitian berkisar dari 4 Maret 2020 hingga 17 April 2020. Pengujian dilakukan dengan menggunakan uji beda Paired Sample t-test dengan software SPSS 26. Hasil dari penelitian menunjukkan bahwa ada perbedaan return yang signifikan antara sebelum dan setelah pengumuman surat keputusan dewan direksi Bursa Efek Indonesia mengenai perubahan waktu perdagangan tentang transaksi pertukaran, mengenai perkembangan kondisi pasar modal global dan pasar modal Indonesia yang berada di bawah tekanan, antara lain dipengaruhi oleh penentuan virus korona (COVID-19) sebagai pandemi global oleh WHO pada Jakarta Islamic Index (JII).